The Impact of Pecing Pad-Based Service Speed Training on Physical Education Students' Sepak Takraw Service Capabilities at Tadulako University in Palu - sianto, Moh. Ifkhal; abduh, Ikhwan; Agusman, Muhammad; Sardiman, Sardiman; Zainuddin, Erwin (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2025)
Objectives. To enhance the speed of service training through pacing on the sepak takraw service skills of physical education students at Tadulako University, Palu. Materials and Methods. The study involved a total of 8 athletes occupying the roles of servicer or tekong, thus the sample for this research was derived from the complete population of these 8 athletes. Therefore, the sampling technique employs total sampling. The method of data collection involves administering a test, specifically a sepak takraw service speed test. The equipment utilized for the experiment includes a sepak takraw field, a sepak takraw ball, and a stopwatch. The procedure involves measuring the duration from the moment the ball is struck until it makes contact with the floor of the sepak takraw court. Following the pre-test, the sample underwent a service speed training intervention utilizing a pacing pad over the course of 16 sessions. After that, the sample was given a posttest with the same procedure as the initial test or pre-test. Once all the data had been gathered, the next step involved employing the data analysis technique. Results. The data analysis revealed that the investigation into the impact of service speed training utilizing pacing pads on the service speed of sepak takraw athletes at Tadulako University, Palu, yielded significant findings. Conclusion. This study demonstrates that the training method utilizing pacing pads can markedly enhance service speed in sepak takraw. It is advisable to conduct additional studies to investigate the effectiveness of varying training durations, the different applications of pacing pads, and to compare this method with alternative training strategies to enhance athlete performance. Furthermore, studies involving a larger sample size and a broader range of ability levels are necessary to enhance the generalizability of the findings.